Physico-Chemical Explanation of Blood Cell Adhesion in Thrombus Formation - Marmur, A; Ruckenstein, E; Rakower, S. R (Thrombosis and Haemostasis, 1976)
A model is suggested which assumes that the rate of deposition of cells is determined both by hydrodynamic factors and by Brownian motion over the potential barrier caused by London and double-layer forces in the immediate vicinity of the deposition surface. The height of the barrier in the potential energy of interaction between blood cells and various surfaces is analyzed in relation to the physical properties of the cells, surfaces, and solutions. Based on this analysis, the adhesion of platelets to injured blood vessel walls and to non-biologic materials, the lack of adhesion of red blood cells under the same conditions, the mechanism of ADP induced aggregation and the interaction with blood flow are explained. The qualitative predictions of the model are substantiated by available experimental information. Quantitative results are presented in terms of a time constant, which typifies a period of contact with a surface, during which appreciable deposition occurs.